1997
DOI: 10.1111/j.1472-8206.1997.tb00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of trimetazidine on hypoxic cardiac myocytes from the rat

Abstract: The electrophysiological effects of the antianginal drug trimetazidine (TMZ) were investigated in cultured rat ventricular myocytes using a substrate-free hypoxia model of ischemia. The transmembrane potentials were recorded with glass microelectrodes and the contractions were simultaneously monitored with a video motion detector. The cardiomyocytes were treated with TMZ (1-5.10(-4) M final concentration) in the bath. The untreated and the drug-treated cells were submitted either to 150 min normoxia or to 150 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 43 publications
1
10
0
1
Order By: Relevance
“…In patients with acute and chronic coronary artery disease, TMZ is safe and has antianginal and antiischemic clinical effects (Opie and Boucher 1995;Veitch et al 1995;Fantini et al 1997;El Banani et al 2000). Experimentally, it reduces infarct size, decreases platelet aggregation and limits leucocyte influx into the infarct zone (Belcher et al 1993;Williams et al 1993;Noble et al 1995).…”
Section: © 2006 Tohoku University Medical Pressmentioning
confidence: 99%
“…In patients with acute and chronic coronary artery disease, TMZ is safe and has antianginal and antiischemic clinical effects (Opie and Boucher 1995;Veitch et al 1995;Fantini et al 1997;El Banani et al 2000). Experimentally, it reduces infarct size, decreases platelet aggregation and limits leucocyte influx into the infarct zone (Belcher et al 1993;Williams et al 1993;Noble et al 1995).…”
Section: © 2006 Tohoku University Medical Pressmentioning
confidence: 99%
“…Recently it was shown that trimetazidine inhibits long-chain 3-ketoacyl-CoA thiolase (IC 50~ 50 nM) [62]. Trimetazidine is efficient in protecting isolated cardiac myocytes against the functional alterations induced by substrate-free hypoxia and resulted in a better recovery upon reoxygenation [38]. Trimetazidine exhibited also a protective action in cardiomyopathic hamsters.…”
Section: Trimetazidinementioning
confidence: 99%
“…[13][14][15][16] Trimetazidine has been shown to affect myocardial substrate utilization by partially inhibiting oxidative phosphorylation and by shifting energy production from FFAs to glucose oxidation. 17 Recently, it has been reported that TMZ, added to optimal medical therapy in CHF, improves P-w-d in association with improved left ventricular function, 18 delineating potential electrophysiological properties of this drug.…”
Section: Introductionmentioning
confidence: 99%